Household Expenditure in Dental Health Care: National Estimations in Mexico for 2000, 2002, and 2004 - Ricardo Pérez-Núñez, MD, MSc; Armando Vargas-Palacios, Econ, MSc; (Blackwell Synergy, 2007)
To estimate the expenditure on dental care of Mexican households, analyze their trends, and determine the factors associated with the decision to spend and the amount of money spent in 2000, 2002, and 2004.